SPATIAL REGULATION OF PERSONAL BEHAVIOR UNDER CONDITIONS OF THE ACCELERATING COVID-19 PANDEMIC - Khmiliar Оleh; Popovych, Ihor; Hrys, Antonina; Pavliuk, Mariya; Zavatska, Nataliia; Lytvynenko, Olga; Blynova, Olena (Revista Inclusiones, 2020)
The purpose of the study is to examine spatial regulation of personal behavior under conditions of the accelerating COVID-19 pandemic. The research uses proxemics as a symbol of regulation of the research participants’ behavior. It shows that keeping a safe distance has reflected on changes in individual-typological personality traits and on transformation of some nations from “contact” into “distant” ones. The paper substantiates that it is important to know the laws of proxemics language to optimize high-quality interaction. It outlines in a methodological aspect that distance between a sender and a receiver of a message is the most symbolic and relevant feature in the process of interaction. Research results. The study establishes that spatial regulation of personal behavior is significantly affected by such internal symbols as social prestige, introversion-extraversion, the overall volume and content of the message. It proves that that messages with personal and nonpersonal information influence personal behavior regulation. Personal messages are usually transmitted in the intimate and personal spaces. Non-personal messages are transmitted in all four spaces of proxemic interaction: intimate, personal, social and public. The study generalizes that regulation of personal behavior mainly depends on proxemic indexes.